Diurnal Variations in Natriuretic Peptide Levels: Clinical Implications for the Diagnosis of Acute Heart Failure. (7th June 2022) - Breidthardt, Tobias; van Doorn, William P.T.M.; van der Linden, Noreen; Diebold, Matthias; Wussler, Desiree; Danier, Isabelle; Zimmermann, Tobias; Shrestha, Samyut; Kozhuharov, Nikola; Belkin, Maria; Porta, Caroline; Strebel, Ivo; et al.
Abstract : Background: Current guidelines recommend interpreting concentrations of NPs (natriuretic peptides) irrespective of the time of presentation to the emergency department. We hypothesized that diurnal variations in NP concentration may affect their diagnostic accuracy for acute heart failure. Methods: In a secondary analysis of a multicenter diagnostic study enrolling patients presenting with acute dyspnea to the emergency department and using central adjudication of the final diagnosis by 2 independent cardiologists, the diagnostic accuracy for acute heart failure of BNP (B-type NP), NT-proBNP (N-terminal pro-B-type NP), and MR-proANP (midregional pro-atrial NP) was compared among 1577 daytime presenters versus 908 evening/nighttime presenters. In a validation study, the presence of a diurnal rhythm in BNP and NT-proBNP concentrations was examined by hourly measurements in 44 stable individuals. Results: Among patients adjudicated to have acute heart failure, BNP, NT-proBNP, and MR-proANP concentrations were comparable among daytime versus evening/nighttime presenters (all P =nonsignificant). Contrastingly, among patients adjudicated to have other causes of dyspnea, evening/nighttime presenters had lower BNP (median, 44 [18–110] versus 74 [27–168] ng/L; P <0.01) and NT-proBNP (median, 212 [72–581] versus 297 [102–902] ng/L; P <0.01) concentrations versus daytime presenters. This resulted in higher diagnostic accuracy as quantified by the area under the curve of BNP and NT-proBNP among evening/nighttime presenters (0.97 [95% CI, 0.95–0.98] and 0.95 [95% CI, 0.93–0.96] versus 0.94 [95% CI, 0.92–0.95] and 0.91 [95% CI, 0.90–0.93]) among daytime presenters (both P <0.01). These differences were not observed for MR-proANP. Diurnal variation of BNP and NT-proBNP with lower evening/nighttime concentration was confirmed in 44 stable individuals ( P <0.01). Conclusions: BNP and NT-proBNP, but not MR-proANP, exhibit a diurnal rhythm that results in even higher diagnostic accuracy among evening/nighttime presenters versus daytime presenters. Registration: URL: https://www.clinicaltrials.gov ; Unique identifiers: NCT01831115, NCT02091427, and NCT02210897.